Defamation Strategy Implementation in the German Political Discourse - A. P. Kryachkova (Vestnik MGIMO-Universiteta, 2015)
The main definitions of political discourse are introduced in this article. The author also suggests her own definition of this term. The participants of political discourse use various communicative strategies in order to influence opponents. The article reviews various definitions of communicative strategy term. The author gives her own definition of communicative strategy term and describes the main political discourse strategies. The purpose of the article is to review defamation strategy implementation and to identify its role in political discourse of Germany based on Bundestag's political wrangling. The author describes the main tactics and conversational turns of defamation strategy and its development in German politicians' speech image. Defamation strategy is one of the leading strategies in any aggressive verbal behavior discourse. The research describes main communicant's intentions by using of defamation strategy. The addresser uses this kind of strategy to offend the opponent's positive image aiming to undermine opponent's credibility and to reduce his significance at the political stage. There are following tactics of defamation strategy: offence, accusation, jeer. The article reviews the functioning of named tactics in political discourse of Germany. The article describes special aspects of above listed tactics, distinguishes terms of offence and accusation, gives examples from Bundestag's political speeches. Every tactic has its conversational turns, that are realized by various linguistic means. The article analyses political comments as an evaluative lexis subject. It also suggests analysis of such turns as intensification, comment's metaphoricity, comparative constractions, that promote better perlocutionary effect.